2021
DOI: 10.1186/s12544-021-00488-0
|View full text |Cite
|
Sign up to set email alerts
|

Who continued travelling by public transport during COVID-19? Socioeconomic factors explaining travel behaviour in Stockholm 2020 based on smart card data

Abstract: Introduction The COVID-19 pandemic has changed travel behaviour and reduced the use of public transport throughout the world, but the reduction has not been uniform. In this study we analyse the propensity to stop travelling by public transport during COVID-19 for the holders of 1.8 million smart cards in Stockholm, Sweden, for the spring and autumn of 2020. We suggest two binomial logit models for explaining the change in travel pattern, linking socioeconomic data per area and travel data with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 28 publications
5
45
0
1
Order By: Relevance
“…We also found that the car owners significantly prioritized pandemic-related factors when determining their travel mode during the pandemic compared to non-car-owners. Previous studies have also discussed similar issues in that car owners tended to use their private car for commuting from home to work during the pandemic, indicating that people placed a higher priority on their health and comfort over the economy [36,80]. Furthermore, when determining a mode of travel during the pandemic, the findings show that married people and essential workers put a higher priority on pandemic-related factors than single and nonessential workers.…”
Section: Discussionmentioning
confidence: 60%
“…We also found that the car owners significantly prioritized pandemic-related factors when determining their travel mode during the pandemic compared to non-car-owners. Previous studies have also discussed similar issues in that car owners tended to use their private car for commuting from home to work during the pandemic, indicating that people placed a higher priority on their health and comfort over the economy [36,80]. Furthermore, when determining a mode of travel during the pandemic, the findings show that married people and essential workers put a higher priority on pandemic-related factors than single and nonessential workers.…”
Section: Discussionmentioning
confidence: 60%
“…Most of the previous studies described the early impacts of COVID-19 on travel behavior and preferences, focusing on the period before the summer of 2020 ( Abdullah et al, 2020 ; Dingil and Esztergár-Kiss, 2021 ; Dong et al, 2021 ; Eisenmann et al, 2021 ; Hensher et al, 2021 ; Kolarova et al, 2021 ; Shamshiripour et al, 2020 ; Zhang et al, 2021 ). The first studies considering the evolution of the pandemic after that period, characterized by new waves of infection, but also by an increasing adaptation of the population and by advances in the knowledge, prevention, and treatment of the disease, are now coming in ( Almlöf et al, 2021 ; Rothengatter et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research of COVID-19 impact is moving fast, but to the best of the authors' knowledge, this is the first study that applies this modelling framework to analyze the uptake of commuting trips in a “new normal” context, in which the infection rates are still high but the mobility restrictions are less severe or, at least, more locally targeted. Additionally, compared to revealed preferences ( Almlöf et al, 2021 ), the stated preference survey design implemented in this study aims for an improved knowledge about the commuters’ expectations and requirements regarding social distancing on board the PuT, supporting user-centric policies in the post-pandemic future.…”
Section: Introductionmentioning
confidence: 99%
“… 5 An interesting investigation regarding pandemic implications for Stockholm, Sweden, is reported on https://people.kth.se/~jenelius/corona_pt/ (see also Almlöf et al. 2021 ) and in general on https://www.transformative-mobility.org/news/the-covid-19-outbreak-and-implications-to-public-transport-some-observations , last access March 18, 2022. …”
mentioning
confidence: 99%